Effect of some ions on sperm activation in Brycon henni (EIGENMANN 1913) (2007)
ABSTRACT: Spermatozoa in Characid fish remain immobile in seminal plasma and are activated when freed into water where the ionic balance seems to be the main factor starting the activation process. This process was the target of the present study with emphasis on the activation of motility and on motility maintenance over time. The effect of isosmotic solutions was analyzed taking into account the possible combinations of the following ions, Ca2, K', Mg2 and Na' as well as the effect of channel blocking agents. The parameters measured were cells with motility (%), duration of motility (s), plasma membrane potential, and the effect of channel blockers on activation time and on motility. There was an increased motility when the semen was incubated in solutions containing K' (p<0.05) compared with the control (CaNaMgK solution); the longest duration of motility was attained when the incubation was performed in solutions containing Na and Mg2 (p<O.OS). All solutions induced a change in membrane potential detected after 15 s of activation. Blocking K', Ca2, and Na channels did not alter motility but decreased the activation time (p<0.05). Potassium induced activation at all concentrations up to 105 mM, but motility was drastically decreased at concentrations higher than 140 mM (p<0.05). The conclusion is that interaction of the ionic environment with the cell membrane leads to changes in membrane potential and intracellular signalling that trigger sperm motility in Brycon henni